Pendampingan Redesign Pembelajaran Masa Pandemi Covid-19 bagi Tenaga Pendidik di Lembaga Pendidikan berbasis Pesantren di Jawa Timur - Muh Barid Nizarudin Wajdi; M Burhanuddin Ubaidillah; Sri Mulyani; Khoirul Anwar; Lailatul Istiqomah; Fauziyah Rahmawati; Sholihatul Atik Hikmawati; Diah Retno Ningsih; Hasan Syaiful Rizal (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2020)
Education has been one of the most affected sectors since the corona pandemic. Like many countries affected, the Indonesian government has taken several precautions needed to reduce the spread of the virus. This causes obstacles in all educational activities, especially in the teaching and learning process. This article aims to illustrate assistance in redesigning learning model in this pandemic period by applying an online service-learning approach. The results show that educators are given many choices of online media that can be used for the teaching and learning processes, ranging from social media (WhatsApp and Facebook), learning management systems media (google classroom, Edmodo), and video conferencing (Zoom, google meet). In redesigning this learning model, educators mostly used WhatsApp as the main media in delivering the material in online classes, while the Google Classroom LMS media was used for managing the students' assignments